LVIV – CENTER OF RENAISSANCE CULTURE IN UKRAINE - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article discusses the following aspects of the formation of the Ukrainian culture of the Renaissance: the perception of achievements of Renaissance humanist culture of Europe, the emergence of a new cultural paradigm for example kulturotvorcheskih processes in Lviv.